Perancangan Sistem Layanan Pemesanan Online pada Warung Bakso Bacok Sarina Berbasis Web - Qanitah Taqwa; Abdul Khaliq; Supiyandi (CV. Hawari, 2026)
The rapid advancement of digital technology requires Micro, Small, and Medium Enterprises (UMKM) to adapt to the implementation of web-based systems in order to improve efficiency and service quality. Warung Bakso Bacok Sarina is one of the culinary businesses that still implements a manual ordering process, which often causes problems such as long queues. This study uses the Waterfall method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance to reduce the risk of errors in website design. The research was conducted to design a web-based online ordering system to make it easier for customers to place orders and improve the operational efficiency of Warung Bakso Bacok Sarina.